2014
DOI: 10.1016/j.smim.2014.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Chemokines in tuberculosis: The good, the bad and the ugly

Abstract: Mycobacterium tuberculosis (Mtb) infects about one third of the world’s population, with a majority of infected individuals exhibiting latent asymptomatic infection, while 5–10% of infected individuals progress to active pulmonary disease. Research in the past two decades has elucidated critical host immune mechanisms that mediate Mtb control. Among these, chemokines have been associated with numerous key processes that lead to Mtb containment, from recruitment of myeloid cells into the lung to activation of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
75
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(77 citation statements)
references
References 80 publications
1
75
0
1
Order By: Relevance
“…The pyogranulomatous lesion may be surrounded by a layer of endothelial macrophages that may be secreting the same inflammatory cytokines. Support for parts of the model of the pyogranulomatous lesion was also from previous reported animal model studies of melioidosis [29][30][31][33][34][35] and tuberculosis [70][71][72]. There are some similarities between the pyogranulomatous lesions seen in the chronic murine model and lesions reported in humans with chronic melioidosis [30,73].…”
Section: Discussionmentioning
confidence: 63%
“…The pyogranulomatous lesion may be surrounded by a layer of endothelial macrophages that may be secreting the same inflammatory cytokines. Support for parts of the model of the pyogranulomatous lesion was also from previous reported animal model studies of melioidosis [29][30][31][33][34][35] and tuberculosis [70][71][72]. There are some similarities between the pyogranulomatous lesions seen in the chronic murine model and lesions reported in humans with chronic melioidosis [30,73].…”
Section: Discussionmentioning
confidence: 63%
“…These studies also indicate that a better understanding of this aspect of immunity could improve vaccine development and drug treatment. 5,208,209 Cytokines embody both good and bad roles in TB, because they can have context-dependent protective and pathologic consequences. 5 Monin and Khader 208 similarly suggested that chemokine responses can be both good and bad, and that protection in TB is a trade-off between immune control and bacterial replication mediated by appropriately calibrated responses.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages, the sentinels of innate immune system serve as the primary niche to the pathogen and mediate the early retaliation3. In this regard, chemokines produced by immune cells have been implicated in controlling key processes during mycobacterial infection and in defining the concerted recruitment of various other immune cells like neutrophils, T- and B-lymphocytes to curtail the spread of the pathogen45678.…”
mentioning
confidence: 99%